Pengaruh Preferensi Media Sosial Institusi Terhadap Minat Daftar Camaba Ilmu Komunikasi - Khoirunnisa, Alifah; Prabawati, Alodia Bidara (Lenvari: Journal of Social Science, 2024)
Social Media can help prospective new students to find the information needed as a consideration for choosing a major. This study aims to examine the effect of institutional social media preferences on the interest in registering prospective new students majoring in Communication Science, State University of Malang. This research is a quantitative approach that uses a survey method of 200 respondents in data collection. The research subjects were 12th grade high school students in East Java who wanted to continue to the university level as prospective new students majoring in Communication Science who were randomly selected by designing a questionnaire of questions related to social media preferences and interest in enrolling students in the Communication Science department through google form. In this study, researchers used the basic theory of the Technology Acceptance Model (TAM) in determining 3 factors that influence the use of a system: Perceived Usefulness, Perceived Ease of Use, and Intention To Use. Based on the results of the analysis, Social Media Preference contributes to a significant influence on Register Interest by 41%, and the remaining 59% is explained by other variables, which means that Social Media has a partially significant effect on Register Interest.